TNF‐α‐mediated ER stress causes elimination of Mycobacterium fortuitum reservoirs by macrophage apoptosis. Issue 7 (26th February 2018) - Oh, Sung‐Man; Lim, Yun‐Ji; Choi, Ji‐Ae; Lee, Junghwan; Cho, Soo‐Na; Go, Dam; Kim, Seon‐Hwa; Song, Chang‐Hwa
Abstract : Mycobacterium fortuitum (MF), a rapidly growing nontuberculosis mycobacterium, is recognized as an important human pathogen. We investigated whether the endoplasmic reticulum (ER) stress response is associated with the apoptosis of MF‐infected macrophages. The expression of ER molecular chaperones was significantly induced by MF infection. We found that MF‐induced reactive oxygen species (ROS) generation plays a critical role in the induction of ER stress‐mediated apoptosis. Excess TNF‐a in the ER led to ER stress‐mediated apoptosis during MF infection. The intracellular survival of MF was significantly increased by TNF‐α knockdown compared with the control. This is the first report of MF‐induced TNF‐α as a cause of ER stress in macrophages. Furthermore, we found that TLR2‐mediated ER stress response contributed to the elimination of intracellular MF in vivo. These results suggest that TNF‐α‐mediated ER stress during MF infection contributes to the suppression of intracellular survival of MF in macrophages. Our findings provide new insight into the importance of ER stress in mycobacterial infection.—Oh, S.‐M., Lim, Y.‐J., Choi, J.‐A., Lee, J., Cho, S.‐N., Go, D., Kim, S.‐H., Song, C.‐H. TNF‐α‐mediated ER stress causes elimination of Mycobacterium fortuitum reservoirs by macrophage apoptosis. FASEB J. 32, 3993–4003 (2018). www.fasebj.org